On the potential for using selected PCA-based methods to analyze the crime rate in Poland - Misztal, Małgorzata (O możliwości wykorzystania wybranych metod analizy danych opartych na PCA do badania poziomu przestępczości w Polsce, 2019)
The aim of the paper is to assess the potential for using some selected PCA-based methods to analyze the spatial diversity of crime in Poland during 2000-2017. Classical principal components analysis (PCA) deals with two-way matrices, usually taking into account objects and variables. In the case of data analyzed in the study, apart from two dimensions (objects – voivodships, variables – criminal offences), there is also the dimension of time, so the dataset can be seen as data cube: objects × variables × time. Therefore, this type of data requires the use of methods handling three-way data structures. In the paper the variability of some selected categories of criminal offences in time (2000- -2017) and space (according to voivodships) is analyzed using the between-class and the within-class principal component analysis. The advantage of these methods is, among others, the possibility of the graphical presentation of the results in two-dimensional space with the use of factorial maps
Econometrics = Ekonometria, 2019, Vol. 23, No. 2, s. 15-32
Keywords: crime; criminal offence; multivariate exploratory data analysis; principal component analysis; factorial maps; przestępczość; przestępstwa kryminalne; wielowymiarowa eksploracyjna analiza danych; analiza głównych składowych; mapy czynnikowe